Euphorbia bicolor (Euphorbiaceae) Latex Phytochemicals Induce Long-Lasting Non-Opioid Peripheral Analgesia in a Rat Model of Inflammatory Pain - Basu, Paramita; Tongkhuya, Sirima A.; Harris, Taylor L.; Riley, Angela R.; Maier, Camelia; Granger, John; Wojtaszek, Jennie; Averitt, Dayna L. (Frontiers in Pharmacology, 2019)
The negative side effects of opioid-based narcotics underscore the search for alternative non-opioid bioactive compounds that act on the peripheral nervous system to avoid central nervous system-mediated side effects. The transient receptor potential V1 ion channel (TRPV1) is a peripheral pain generator activated and sensitized by heat, capsaicin, and a variety of endogenous ligands. TRPV1 contributes to peripheral sensitization and hyperalgesia, in part, via triggering the release of proinflammatory peptides, such as calcitonin gene-related peptide (CGRP), both locally and at the dorsal horn of the spinal cord. Ultrapotent exogenous TRPV1 agonists, such as resiniferatoxin identified in the latex of the exotic Euphorbia resinifera, trigger hyperalgesia followed by long lasting, peripheral analgesia. The present study reports on the analgesic properties of Euphorbia bicolor, a relative of E. resinifera, native to the Southern United States. The study hypothesized that E. bicolor latex extract induces long-lasting, non-opioid peripheral analgesia in a rat model of inflammatory pain. Both inflamed and non-inflamed adult male and female rats were injected with the methanolic extract of E. bicolor latex into the hindpaw and changes in pain behaviors were reassessed at various time points up to 4 weeks. Primary sensory neuron cultures also were treated with the latex extract or vehicle for 15 minutes followed by stimulation with the TRPV1 agonist capsaicin. Results showed that E. bicolor latex extract evoked significant pain behaviors in both male and female rats at 20 minutes post-injection and lasting around 1-2 hours. At 6 hours post-injection, analgesia was observed in male rats that lasted up to 4 weeks, whereas in females the onset of analgesia was delayed to 72 hours post-injection. In sensory neurons, latex extract significantly reduced capsaicin-evoked CGRP release. Blocking TRPV1, but not opioid receptors, attenuated the onset of analgesia and capsaicin-induced CGRP release. Latex was analyzed by mass spectrometry and eleven candidate compounds were identified and reported here. These findings indicate that phytochemicals in the E. bicolor latex induce hyperalgesia followed by peripheral, non-opioid analgesia in both male and female rats, which occurs in part via TRPV1 and may provide novel, non-opioid peripheral analgesics that warrant further examination.